Study on Chemical Composition of Fresh Mymensingh and Barishal Hog-plum (Spondius mangifera) and Developed Leather and Jelly and Sensory Evaluation (Journal of Environmental Science and Natural Resources, 2013)
The study was concerned with the chemical composition of two varieties hog-plum Pulp collected from Mymensingh and Barishal and developed jelly and leather. Cabinet dryer, model OV-165 (Gallen Kamp Company) was used for dehydration of two types of hog-plum pulp and leather. The fresh and dried hog-plum and hog-plum products were analyzed for their moisture, ash, vitamin-C, pH, total soluble solids and sucrose contents. The moisture content, ash, vitamin C, pH, total soluble solid (TS), reducing sugar and non-reducing sugar of Barishal hog-plums was 83.84% (wb), 0.81% , 33.00 mg/100g, 2.62, 8.5%, 5.02% and 1.6% respectively; Mymensingh hog-plums was 86.69% (wb), 0.78%, 30.90 mg/100g, 2.7, 6.5%, 4.7% and 1.3% respectively. The chemical composition of Mymensingh and Braishal hog-plum showed that Barishal hog-plum contained higher solid content, ash, Vitamin C than Mymensingh hog-plum. It was found that Barishal hog-plum had higher flesh (67.59%) than Mymensingh hog-plum (62.60%). The chemical composition of hog-plum leather was analyzed for moisture, Ash, Vitamin C, TS, Titrable acidity, total sugar and protein content. The ash and sugar content of developed leathers from Barishal and Mymensingh hog-plum was very similar but the vitamin C content for developed products was very low. It was also found developed products contained higher amount and sugar and protein. It was found that the chemical compositions of developed jelly were more or less similar to the fresh hog-plum; only the vitamin C was decreased significantly. These studies indicate that, developed products viz. lather and jelly would contain significantly higher amount of nutrients and energy then the fresh fruits. Organoleptic taste testing using 1-9 hedonic scale showed that jelly made from mechanically dried Mymensingh hog-plum was the most acceptable product and was ranked as like very much. Leather made from Mymensingh hog-plum (pulp+4.5% sugar+ 0.15% KMS) was the best among other samples and was ranked as like very much.DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14598 J. Environ. Sci. & Natural Resources, 5(2): 29-36 2012